The Influence of Price Discount and Customer Experience on Customer Loyalty to Customers of the Juragan Tepi Sawah Restaurant in Palopo City - Achmad Efendi; Muammar Khaddapi; Salong Salong (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The purpose of this study was to analyze the effect of price discount and customer experience towards customer loyalty at the Jurangan Tepi Sawah Restaurant in Palopo City. This study uses primary data, namely data taken directly from the main source. The data analysis of this research used multiple linear regression using SPSS (Statistical Program for Social Science) tool .The results of this research show that : (1). Variable p rice d account positive and significant effect on customer loyalty to the customer Jurangan Tepi Sawah Restaurant in Palopo City. ( 2 ) .Customer experience variable positive and significant effect on customer loyalty to the customer Jurangan Tepi Sawah Restaurant in Palopo City.